ANALYSIS OF DESTINATION IMAGE AND SOCIAL MEDIA MARKETING MODELS IN FORMING TOURIST LOYALTY: A STUDY OF DEVELOPING DESTINATIONS IN INDONESIA - Lumanauw, Nelsye; Kusuma, Rr. Chusnu Syarifa Diah; Goyal, Mukta; Sudirman, Acai (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This study aims to analyze the role of destination image, social media marketing, and tourist satisfaction in shaping tourist loyalty and developing tourist destinations in Indonesia. Using a quantitative approach through a survey of domestic and foreign tourists, this study examines how perceptions of destination image and the effectiveness of social media marketing contribute to tourist satisfaction, which ultimately influences their intention to return and recommend the destination. Data were collected through an online questionnaire, and regression tests, hypothesis tests, correlation tests, and coefficient of determination models were used to examine the relationship between the variables studied. The results show that destination image, social media marketing, and tourist satisfaction significantly affect loyalty. These findings emphasise the importance of authentic digital marketing strategies and strengthening positive destination images to maintain and increase tourist visits sustainably. This study provides practical implications for tourism destination managers in Indonesia in designing more effective promotional policies and strengthening positive tourist experiences as the key to building long-term loyalty.